Analytical and numerical studies of vertical anchor plates in cohesion less soils - Kassim, Khairul Anuar (2010)
A history of theoretical and numerical studies of vertical anchor plates for the last sixty years iscritically reviewed. To estimate the ultimate pullout capacity of vertical anchor plates a number ofanalytical and numerical methods, have been developed. Vertical anchor plates are used in differentapplications including seawall, retaining wall, excavations and etc. In the article takes place adiscussion based on different theories and numerical studies in vertical anchor plates done by previousresearchers. Analysis, beginning from Terzaghi (1943) until the most recent analysis are reviewed.This analysis was pioneered by Hansen (1953), Ovesen (1964), Biarez et al. (1965), Meyerhof (1973),Neely (1973), Das (1975) and Rowe and Davis (1982), Hanna (1998), Murray and Geddes (1989),Basudhar and Singah (1994), Merifield, Sloan and Yu (2006) are also discussed. The conclusion showsthat previous theories and numerical studies agree closely with the results of experimental works.